The evolution of the development of forest amelioration land use and restoration of field protection forest strips in communities - Sharyi, G.; Kuznetsova, O.; Odaryuk, T.; Yermakova, I.; Shara, S. (Land Management, Cadastre and Land Monitoring, 2024)
The work examines the evolution of the development of field-protecting forest strips (forest strips), the main component of the agro-landscapes of the steppe and forest-steppe of Ukraine, as well as the determined directions for the preservation of forest strips and the need to involve communities and the public in afforestation and restoration works. One of the basic elements of preserving the productivity of agricultural landscapes, protecting soils from wind and water erosion. The importance of forest strips as an important element of the ecological framework of the steppe and forest-steppe of Ukraine, which ensures a 20% increase in crop yields, forms a special microclimate in the agricultural sphere, and improves soil water supply, is emphasized. The unsatisfactory and partly critical condition of the forest belts of Ukraine, especially in the combat zones, was determined, and possible legal and regulatory solutions at the state, regional and local levels were proposed. The need to strengthen state support for land afforestation and insufficient government measures in the field of afforestation are emphasized. The paper proposes measures and mechanisms for solving the problem of protection, restoration and development of the forest belt system, which is relevant for Ukraine, and increasing the percentage of forests in the steppe and forest-steppe of Ukraine, due to forest reclamation. Problems affecting the functioning of forest strips and their protective functions are described. It is proposed to transfer agroforests removed from collective property lands and created by the efforts of villages to communities as an incentive for the organization of communal forestry units in communities, which will make it possible to consolidate and revitalize most forest strips and carry out afforestation of communal and private land plots. The need to adopt state and regional target programs for the protection and development of forest plantations has been determined Land payments to the budget, with the allocation of up to 50 percent of land payments from agricultural lands to the specified goals, have been identified as the main source of financing for forest reclamation works, restoration of forest strips and afforestation. It was noted that agricultural producers who implement the methods of intelligent, combined and organic farming in most cases carefully take care of forest strips and maintain their functional properties. In the Poltava region, we can single out the enterprises "Astarta-Kyiv" and PE "Agroekology". Keywords: field protection forest strips, land use, communities, revitalization, afforestation, agricultural landscapes, land protection, organic farming, forest reclamation.